Helpful behaviour and the befrienders / Loke Khoon Ee - Loke , Khoon Ee (1981)
This academic exercise is an at tempt to study the helpful behaviour of the Befrienders and whether individual differences, such as sex, age, academic achievement level, birth order, race and social class, affect their helpful behaviour. For this purpose, questionnaires were given to the volunteers at the Counselling Centres of the Befriender in Petaling Jaya and Penang. There were 43 respondents (37. 2% male, 62. 8% female) and 18 respondents (50% of each sex) from the respective centres. The findings of t his study generally showed that there was a higher proportion of female respondents. Mo st of the respondents came from the 21- 30 age group, and with Form 4-5 level of education. Most of them were Chinese and also older siblings. The high social class respondents predominated the other classes. The cost of helping, time spent and being away from home and family, did not seem to be high for most of the respondents . The majority had done some voluntary work before, but had not received help from either the Befriendore or other voluntary organisation. Most of them did not have encouragement from friends of family to join the Befriendore, but had members of The family involved in it. Their own experience seemed to be The the main factor that made them volunteers. Most of them believed in helping others and reciprocating help. Befriending was considered rewarding by the majority, who believed that it affected their relationship with family and friends positively.